2022
DOI: 10.3389/fcvm.2022.952114
|View full text |Cite
|
Sign up to set email alerts
|

SR9009 improves heart function after pressure overload independent of cardiac REV-ERB

Abstract: The core clock component REV-ERB is essential for heart function. Previous studies show that REV-ERB agonist SR9009 ameliorates heart remodeling in the pressure overload model with transverse aortic constriction (TAC). However, it is unknown whether SR9009 indeed works through cardiac REV-ERB, given that SR9009 might target other proteins and that REV-ERB in non-cardiac tissues might regulate cardiac functions indirectly. To address this question, we generated the REV-ERBα/β cardiac-specific double knockout mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…Similar results were seen in both CFs and MEFs. Our results corroborated with previous reports and showed that SR9009 likely has off-target effects that contribute to its cardiac protective and anti-fibrotic functions ( Dierickx et al, 2019 ; Li et al, 2022 ). A more detailed study to identify the possible mechanisms and targets of SR9009 is beyond the scope of the current study.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Similar results were seen in both CFs and MEFs. Our results corroborated with previous reports and showed that SR9009 likely has off-target effects that contribute to its cardiac protective and anti-fibrotic functions ( Dierickx et al, 2019 ; Li et al, 2022 ). A more detailed study to identify the possible mechanisms and targets of SR9009 is beyond the scope of the current study.…”
Section: Discussionsupporting
confidence: 93%
“…Another REV-ERB agonist GSK4112 inhibits myofibroblasts activation in idiopathic pulmonary fibrosis (IPF) fibroblasts ( Cunningham et al, 2020 ). However, SR9009 has REV-ERB–independent effects in the mouse hepatocytes, embryonic stem cells and cardiomyocytes ( Li et al, 2022 ) ( Dierickx et al, 2019 ). Therefore, it is unclear whether REV-ERB has a cell-autonomous function in fibroblasts and whether the effect of SR9009 in fibroblasts is dependent on REV-ERB.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating research has firmly established that the circadian clock could be a novel therapeutic target for muscular dystrophy [27,54,56,58,153]. The molecular mechanisms underlying clock modulation of muscle mass, function, growth, and repair provide the mechanistic basis for exploring pharmacological interventions of clock activity to ameliorate dystrophic disease.…”
Section: Recent Progress In Discovering Circadian Clock Modulators Wi...mentioning
confidence: 99%